Recurrent Pneumonias and Bronchiectasis - Is it an Immunodeficiency Disorder? - A Case Report - Agrawal, Sumit; Shreeram, S; Jha, A; Prajapati, B (Journal of Nepal Paediatric Society, 2020)
Common Variable Immunodeficiency (CVID) is a form of primary immunodeficiency disorder characterised by hypogammaglobulinemia and recurrent sino-pulmonary infections. Its diagnosis is based on the presence of low serum IgG (< 2 SD below normal for age) with or without low IgA/ IgM levels and presentation beyond two years of age. These children also have disorders of autoimmunity with majority of them presenting as autoimmune cytopenias, predominantly thrombocytopenia and some having anaemia and neutropenias. Here we report a nine years old boy with past history of recurrent pneumonia, presenting this episode with fungal pneumonia, thrombocytopenia and anaemia eventually diagnosed as CVID.